Effects of dietary Tenebrio molitor meal inclusion in free‐range chickens. Issue 6 (23rd March 2016) - Biasato, I.; De Marco, M.; Rotolo, L.; Renna, M.; Lussiana, C.; Dabbou, S.; Capucchio, M. T.; Biasibetti, E.; Costa, P.; Gai, F.; Pozzo, L.; Dezzutto, D.; et al.
Summary: Insects are currently being considered as a novel protein source for animal feeds, because they contain a large amount of protein. The larvae of Tenebrio molitor (TM) have been shown to be an acceptable protein source for broiler chickens in terms of growth performance, but till now, no data on histological or intestinal morphometric features have been reported. This study has had the aim of evaluating the effects of dietary TM inclusion on the performance, welfare, intestinal morphology and histological features of free‐range chickens. A total of 140 medium‐growing hybrid female chickens were free‐range reared and randomly allotted to two dietary treatments: (i) a control group and (ii) a TM group, in which TM meal was included at 75 g/kg. Each group consisted of five pens as replicates, with 14 chicks per pen. Growth performance, haematological and serum parameters and welfare indicators were evaluated, and the animals were slaughtered at the age of 97 days. Two birds per pen (10 birds/treatment) were submitted to histological (liver, spleen, thymus, bursa of Fabricius, kidney, heart, glandular stomach and gut) and morphometric (duodenum, jejunum and ileum) investigations. The inclusion of TM did not affect the growth performance, haematological or serum parameters. The morphometric and histological features were not significantly affected either, thus suggesting no influence on nutrient metabolization, performance or animal health. Glandular stomach alterations (chronic flogosis with epithelial squamous metaplasia) were considered paraphysiological in relation to free‐range farming. The observed chronic intestinal flogosis, with concomitant activation of the lymphoid tissue, was probably due to previous parasitic infections, which are very frequently detected in free‐range chickens. In conclusion, the findings of this study show that yellow mealworm inclusion does not affect the welfare, productive performances or morphological features of free‐range chickens, thus confirming that TM can be used safely in poultry diets.